The image of the hero in modern Ukrainian cinema: moral and sociocultural collisions of creation - Tymoshenko, Alyona (Ukrainian Cultural Studies, 2024)
Background. The relevance of research lies in the fact that a wide spectrum of characters created by contemporary cinema become symbols of their time and culture. Analyzing such heroes’ images allows us to uncover the depth of their moral, sociocultural, and psychological aspects that reflect the trends and values of contemporary society. Methods. The method of interview is used in the research, and the optics of the texts by Carl Jung and Joseph Campbell were used to conceptualize the material. Investigating the cinematic creation of hero’s image reveals the methods and strategies used by authors to achieve depth and realism in their characters. Specifics of such processes are crucial for understanding how cinema shapes our consciousness and influences our perception of present-day reality. Unveiling the creation of heroic imagery in cinema is significant both for analyzing contemporary culture and for finding ways to resolve conflicts and build peace. In the current global transformations and turbulency, in the third year of russian full-scale invasion of Ukraine, cultural issues are extremely important, as they play a vital role in forming new meanings and connections, national self-identity, and intercultural understanding. Objective. To investigate the process of hero’s image creation in cinema, including the methods, strategies, and techniques used by authors to achieve depth and realism in their characters; and to highlight the importance of studying film characters in the context of contemporary challenges such as wars, conflicts, and social changes. Results. The research identifies the main stages and methods of hero’s image creation, reveals the influence of authorial decisions on the process of hero transformation/creation, and determines which specific filmmakers’ choices affect the development and change of the hero’s image throughout the film. The analysis uncovers the significance of moral, sociocultural, and psychological aspects in the process of hero’s image transformation/creation. Presented analysis of cinematic masterpieces illustrates the process of hero’s image transformation through the path of creation. Conclusions. The processes of hero’s image creation and transformation in contemporary cinema have an important impact on culture and society, especially in challenging circumstances, and need further investigations by cultural studies.